Assessing Risk before Departure: Risk Perception and Decision-Making of Prospective Indonesian Migrant Workers - Arbania Fitriani; Tohirin; Ety Nurhayati (Wardah, 2026)
This study aims to analyze the influence of risk perception on the decision-making of prospective Indonesian migrant workers (CPMI) in the pre-departure phase. The growing public interest in working abroad is often not accompanied by an adequate understanding of the potential risks. This study offers novelty by empirically integrating the Theory of Planned Behavior and the Risk-as-Feelings Framework within the specific pre-departure migration context, demonstrating that risk perception functions as a significant cognitive–affective predictor of rational decision-making among prospective Indonesian migrant workers.This study uses a quantitative, correlational design. Participants were 150 prospective migrant workers who attended training at five Job Training Institutions (LPK) in Indonesia. The research instrument consisted of the Perceived Risk Factors for Pre-departure Migrant Workers Scale (PD-RFPS) and the Quality of Decision-Making Orientation Scheme (QoDoS), both of which demonstrated high reliability (α = 0.913 and α = 0.950, respectively). Data analysis was performed using simple linear regression in SPSS. The results showed that risk perception significantly affected the decision-making of prospective migrant workers (R² = 0.446; p < 0.05). The higher an individual's perception of risk, the more rational and careful their decision-making process is. These findings strengthen the Theory of Planned Behavior and the Risk-as-Feelings Framework by emphasizing the role of interactions between cognitive and affective processes in the context of work migration. In practice, this study's results highlight the importance of risk perception education and strengthening psychological literacy in pre-departure training for migrant workers to improve mental readiness and work safety abroad.